(untitled) (Raparin Journal of Humanities (RJH), 2026)
It is obvious that change is widespread in all aspects of language; therefore, it is essential to take this fact into account when dealing with all levels of language. Phoneme change refers to those that happen according to the phonotactic rules of a particular language. In such changes, the occurrence of consonants and vowels play a great role in constructing the syllables. In fact, language is made up of a sound system, the larger units such as morphemes and words are the result of the systematic combination of the phonemes. As compared to the other levels of language, the sound level is more liable to change in a way some think that when a change happens in a particular position in a word it also Happen in all other similar positions in other words. The purpose of doing this paper is to deal with phonemes in the framework of optimality theory in Pishdar accent. The data of the paper consist of the samples taken from the accent, collected, and then analyzed. For this purpose, more than 60 speakers over 16 years of age in Pishdar district have been interviewed. The samples have been gathered and arranged according to IPA symbols and they have been analyzed finally. The method used in doing the research is descriptive-analytic focusing on the change that phonemes undergo, especially the consonants. One of the concluding remarks is that phoneme change is considered to a great extent in Pishdar accent.